Guided Translation to Channel an Autistic Learner’s Potentials in L2 Writing: A Case Study - Subekti, Adaninggar Septi (FKIP Universitas Lampung, 2020)
Guided Translation to Channel an Autistic Learner’s Potentials in L2 Writing: A Case Study. Objectives: This study aimed to investigate to what extent the use of guided translation from the Indonesian language into English could facilitate a student with Autism Spectrum Disorder (ASD) to write a five-paragraph descriptive essay and expository essay in English. Methods: The study used observations on the participant’s learning behaviours and qualitative document analysis of the participant’s essays during the period of one semester. Findings: The use of guided translation helped the autistic learner, who typically had difficulty in language production both in L1 and L2, to write two essays in L2, whose overall quality analysed using the grading rubrics, was relatively the same as those of his developing peers, albeit the participant needed much more time. Conclusion: The finding suggested that autistic learners’ L1 could be capitalised to optimise their L2 learning.Keywords: Guided translation, Autism Spectrum Syndrome (ASD), L2 writing, case study.